2023
DOI: 10.1007/s40266-023-01072-y
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Cascades with Recommendations to Prevent or Reverse Them: A Systematic Review

Oriane Adrien,
Atiya K. Mohammad,
Jacqueline G. Hugtenburg
et al.

Abstract: Background To reduce prescribing cascades occurring in clinical practice, healthcare providers require information on the prescribing cascades they can recognize and prevent. Objective This systematic review aims to provide an overview of prescribing cascades, including dose-dependency information and recommendations that healthcare providers can use to prevent or reverse them. Methods The Preferred Reporting Items for Systematic Reviews and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 103 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…These reviews reported multiple examples of prescribing cascades described in the literature. Examples include the prescription of loop diuretics for pedal oedema related to calcium channel blocker prescription and levothyroxine prescribed for amiodarone-induced hypothyroidism [ 15 , 16 ]. An explicit set of prescribing cascades ThinkCascades has recently been published and includes nine clinically relevant prescribing cascades agreed through international expert consensus [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These reviews reported multiple examples of prescribing cascades described in the literature. Examples include the prescription of loop diuretics for pedal oedema related to calcium channel blocker prescription and levothyroxine prescribed for amiodarone-induced hypothyroidism [ 15 , 16 ]. An explicit set of prescribing cascades ThinkCascades has recently been published and includes nine clinically relevant prescribing cascades agreed through international expert consensus [ 17 ].…”
Section: Introductionmentioning
confidence: 99%